Ijtihad Imam Asy-Syafi'i (Analsis Kritis terhadap Qaul Qadim dan Qaul Jadid) - Ubaidillah Ubaidillah (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
Abstract Ijtihad is the gateway to Islamic progress. The rise and fall of Islam is closely linked to the ebb and flow of ijtihad activities. Because the activities of ijtihad make sense in digging into the pearls of knowledge stored in the Qur'an and al-Hadith. The Asi-Shaykh priest was one of the initiators of the sect to establish his own method of legal practice in issuing his fatwa. Some of its Islamic activities are in two different places, Iraq and Egypt. The fatwas that he produced during his reign in Iraq were known as the qaul qadim, while the fatwas he produced in Egypt were known as the qaul qadim. In this study the researchers used a bibliographie research approach and their data collection procedure using editing, coding and tabulating. So the result is that finding qaul qadim can be demonstrated in the case of the ability of a guardian to replace the fasting left by the deceased due to the inclusion of shaheh hadith. Whereas in other cases qaul jadid is featured because it reinforces the quality of the arguments.